Inequalities in the burden of non-communicable diseases across European countries: a systematic analysis of the Global Burden of Disease 2019 study - Andrade, Carlos Alexandre Soares; Mahrouseh, Nour; Gabrani, Jonila; Charalampous, Periklis; Cuschieri, Sarah; Grad, Diana Alecsandra; Unim, Brigid; Mechili, Enkeleint A; Chen-Xu, José; Devleesschauwer, Brecht; Isola, Gaetano; von der Lippe, Elena; et al. (My University, 2023)
Although overall health status in the last decades improved, health inequalities due to non-communicable diseases (NCDs) persist between and within European countries. There is a lack of studies giving insights into health inequalities related to NCDs in the European Economic Area (EEA) countries. Therefore, the aim of the present study was to quantify health inequalities in age-standardized disability adjusted life years (DALY) rates for NCDs overall and 12 specific NCDs across 30 EEA countries between 1990 and 2019. Also, this study aimed to determine trends in health inequalities and to identify those NCDs where the inequalities were the highest.
Keywords: DALY rate; European Economic Area; European Union; Global Burden of Disease; Health inequality; Non-communicable diseases